PERAN DIGITAL BANKING SEBAGAI WUJUD PENERAPAN GREEN BANKING DI ERA SOCIETY 5.0 - Pristanto, Mukhammad Muchyiddin (KINDAI, 2024)
The Indonesian financial services industry is an industry that plays an important role in economic activities. With digital banking, it can make it easier for customers and banks to carry out banking activities as well as a manifestation of implementing environmentally friendly green banking as an effort to be responsible for environmental sustainability. The method used in this research is descriptive qualitative analysis, where all data produced is presented in the form of a description, namely a general description of the research results. The research results show that Digital Banking is a form of implementing Green Banking in the Era of Society 5.0. Keywords: Green Banking, Digital Banking, Technology